Malika: warrior queen (2017), volume 1 ebook - Okupe, Roye (Malika: Warrior Queen (2017), 2021)
Part of the YouNeek YouNiverse!  Extraordinary fantasy and superhero stories inspired by African history, culture, and mythology—created by the best Nigerian comics talent! Following the exploits of queen and military commander Malika, who struggles to keep the peace in her ever-expanding empire, Azzaz, this historical fantasy is set in fifteenth-century West Africa and created by an all-star team from Nigeria.Growing up as a prodigy, Malika inherits the crown from her father in an incredibly unusual way, splitting the kingdom of Azzaz in half. After years of civil war, Malika finally unites all of Azzaz, expanding it into one of the largest empires in all of West Africa--but expansion will not come without its costs. Enemies begin to rise within her council, and Azzaz catches the attention of one of the most feared superpowers the world has ever known: the Ming Dynasty! As Malika fights to win the clandestine war within the walls of her empire, she must also turn her attention to an indomitable and treacherous foe with plans to vanquish her entire people. Malika: Warrior Queen Volume 1 also features bonus stories "Malika: Dragon Trials" and "WindMaker: Birth of a King"—and a new "behind the scenes" section! ""Our mission is and always has been about empowering African creatives and storytelling while bringing both to a global audience."" — Roye Okupe, Founder/Creative Director at YouNeek Studios